The crises of Israeli democracy: political-ideological framings by members of Israel’s 24th Knesset - Yoav Arad; Michael Freedman (Frontiers in Political Science)
This study examines how members of Israel’s 24th Knesset perceive and define democracy, and how their political-ideological identities influence these understandings. Using qualitative analysis of public statements and social media posts from 72 Knesset members, the research reveals a strong correlation between MKs’ ideological-political identities and their framing of democracy. Liberals tended to emphasize substantive democratic values like pluralism and individual rights, while conservatives prioritized a populist notion of majority rule. Religious MKs often viewed democracy through a sectarian lens, subjugating it to Jewish religious principles. Non-Jewish MKs vacillated between liberal and populist stances. The study raises concerns about the depth of commitment to democratic principles among many elected officials and the potential implications for Israeli democracy. It highlights the tension between Israel’s Jewish and democratic identities and suggests that the political landscape is increasingly challenging the vision of Israel’s founders for a democratic state.